Exploring EFL Students of Game Based Activities in Enhancing Their Receptive Skills : Menjelajahi Aktivitas Berbasis Permainan pada Siswa EFL dalam Meningkatkan Keterampilan Reseptif Mereka - Elanneri Karani; Tutik Haryani; Laura Maharani (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This research study explores the effectiveness of game-based activities in developing the receptive skills of learners of English as a Foreign Language (EFL) with a focus primarily, but not exclusively, on listening and reading comprehension. In a climate of limited exposure to authentic English and generally low rates of student engagement, games offer an attractive alternative to traditional teaching.This study adopts a qualitative descriptive design, using a literature review to analyse previous empirical studies from reputable journals involving both traditional and computer-based games. The analysis revealed that traditional games such as Chain Whisper, Whisper Race and Tic Tac Toe effectively improved students’ auditory comprehension, focus and motivation. Additionally, digital games, including America’s Army, Grammarian Android, Classcraft, Quizizz and BTS Island: In the SEOM, are associated with enhanced reading comprehension, vocabulary development, and engagement of learners. The outcomes align with significant language learning theories such as Krashen’s Input Hypothesis, Vygotsky’s Sociocultural Theory, and Self-Determination Theory; specifically, they espouse the idea that comprehension and sustained learning are optimized in contexts where enjoyment is prioritized and there is low anxiety. This study suggests that employing game-based activities in EFL teaching may lead to more meaningful, participatory, and autonomous learning that improves students’ receptive skills and interest in learning English. Keywords: game-based learning, receptive skills, EFL learners, listening comprehension, reading comprehension.